Social conformity is due to biased stimulus processing: electrophysiological and diffusion analyses - Germar, Markus; Voß, Andreas (Social cognitive and affective neuroscience, 2016)
Hundreds of studies have found that humans’ decisions are strongly influenced by the opinions of others, even when making simple perceptual decisions. In this study, we aimed to clarify whether this effect can be explained by social influence biasing (early) perceptual processes. We employed stimulus evoked potentials, lateralized readiness potentials (LRPs) and a diffusion model analysis of reaction time data to uncover the neurocognitive processes underlying social conformity in perceptual decision-making. The diffusion model analysis showed that social conformity was due to a biased uptake of stimulus information and accompanied by more careful stimulus processing. As indicated by larger N1-amplitudes, social influence increased early attentional resources for stimulus identification and discrimination. Furthermore, LRP analyses revealed that stimulus processing was biased even in cases of non-conformity. In conclusion, our results suggest that the opinion of others can cause individuals to selectively process stimulus information supporting this opinion, thereby inducing social conformity. This effect is present even when individuals do not blindly follow the majority but rather carefully process stimulus information.
Gesehen am 29.11.2017